2011
DOI: 10.1007/s12078-011-9103-7
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variability in the Awareness of Odors: Demographic Parameters and Odor Identification Ability

Abstract: Human chemosensation can be strongly influenced by how much attention people pay to chemosensory stimuli (e.g., Marks and Wheeler in Chem Senses 23:19-29, 1998; Prescott et al. in Chem Senses 29:331-340, 2004). In a recent study, a scale has been devised (i.e., the Odor Awareness Scale; OAS; see Smeets et al. in Chem Senses 33:725-734, 2008) to investigate the level of awareness people have of the available odorants in the environment. Here, we explored whether a variant (Italian version) of the OAS could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…The correction for multiple comparisons prevent us to make any strong claims about the effect of gender in OIP, nevertheless the trend of the effects allows us to suggest an advantage for women over men. This would be in accordance with previous studies conducted in our laboratory (see Demattè et al, 2011) and with what has been previously and extensively described in the literature (for review, see Good & Kopala, 2006). No other factor (like age or smoking habits) revealed to exert a significant modulation neither of OIP nor of neophobic attitudes.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The correction for multiple comparisons prevent us to make any strong claims about the effect of gender in OIP, nevertheless the trend of the effects allows us to suggest an advantage for women over men. This would be in accordance with previous studies conducted in our laboratory (see Demattè et al, 2011) and with what has been previously and extensively described in the literature (for review, see Good & Kopala, 2006). No other factor (like age or smoking habits) revealed to exert a significant modulation neither of OIP nor of neophobic attitudes.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, results were also analysed as a function of a number of different demographic parameters (e.g., age, gender, etc.) as previous research demonstrated their relation with chemosensory awareness and performance (Demattè et al, 2011).…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations